2012
DOI: 10.1128/aac.00355-12
|View full text |Cite
|
Sign up to set email alerts
|

Caspofungin Etest Susceptibility Testing of Candida Species: Risk of Misclassification of Susceptible Isolates of C. glabrata and C. krusei when Adopting the Revised CLSI Caspofungin Breakpoints

Abstract: bThe purpose of this study was to evaluate the performance of caspofungin Etest and the recently revised CLSI breakpoints. A total of 497 blood isolates, of which 496 were wild-type isolates, were included. A total of 65/496 susceptible isolates (13.1%) were misclassified as intermediate (I) or resistant (R). Such misclassifications were most commonly observed for Candida krusei (73.1%) and Candida glabrata (33.1%). The revised breakpoints cannot be safely adopted for these two species. The CLSI breakpoints fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 22 publications
4
46
0
Order By: Relevance
“…In addition to providing a strategy for predicting caspofungin susceptibility and resistance among Candida spp., these results provide strong support for concerns regarding the issue of crossresistance between micafungin and caspofungin (5,15,16,18,22,26). By using an extensive global collection of clinically important isolates, including fks mutant strains, we validate concerns originating from single-center case series and rightly focus attention on C. glabrata as the species most likely to demonstrate cross-resistance between these two studied echinocandins.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition to providing a strategy for predicting caspofungin susceptibility and resistance among Candida spp., these results provide strong support for concerns regarding the issue of crossresistance between micafungin and caspofungin (5,15,16,18,22,26). By using an extensive global collection of clinically important isolates, including fks mutant strains, we validate concerns originating from single-center case series and rightly focus attention on C. glabrata as the species most likely to demonstrate cross-resistance between these two studied echinocandins.…”
Section: Resultsmentioning
confidence: 93%
“…Whereas the CLSI has developed clinical breakpoints (CBPs) for anidulafungin, caspofungin, and micafungin against the six most common species of Candida (9), the European Committee on Antimicrobial Susceptibility Testing (EUCAST) has elected to establish CBPs for anidulafungin and micafungin but not for caspofungin (10). Furthermore, the EUCAST does not currently recommend caspofungin MIC testing for clinical decision making due to unacceptably high variation among the caspofungin MIC values obtained from different centers (4,5,11,12). This variation is evident not only using the EUCAST BMD method (4,11) but also using the CLSI method (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lower Etest MIC values than CLSI-BMD MIC values for CAS have also been reported earlier for other Candida species (27). Recently, the performance of the CAS Etest based on the recently revised CLSI breakpoints for Candida isolates showed that 13.1% were misclassified as intermediate or resistant (28). Also, marked interlaboratory variation has been observed with both CLSI-BMD and the EUCAST method for CAS susceptibility (29).…”
Section: Discussionmentioning
confidence: 91%
“…Different degrees of dip effect may affect the MICs of gradient concentration strips, particularly for isolates with CLSI MICs of Յ0.25 mg/liter, as found in the present study in a greater degree with the MTS strips and a lesser degree with the Etest strips. Because the dip effect occurred for isolates with MICs close to the CLSI susceptibility breakpoints for caspofungin, namely, 0.25 mg/ liter for C. albicans, C. tropicalis, and C. krusei and 0.125 mg/liter for C. glabrata, correct MIC determination is very important in order to avoid classification errors in the susceptibility of isolates as previously reported for caspofungin (12).…”
mentioning
confidence: 99%